2015
DOI: 10.3892/or.2015.4515
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of RUNX3 in cancer metastasis (Review)

Abstract: Metastasis remains the major driver of mortality in patients with cancer. The multistep metastatic process starts with the dissemination of tumor cells from a primary site and leading to secondary tumor development in an anatomically distant location. Although significant progress has been made in understanding the molecular characteristics of metastasis, many questions remain regarding the intracellular mechanisms governing transition through the various metastatic stages. The runt-related transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 105 publications
(125 reference statements)
1
56
0
Order By: Relevance
“…The mechanisms by which RUNX3 acts in cervical cancer have not been reported. Transcription factor of RUNX3, which is a downstream effector of TGF-β, acts on the TGF-β receptor type II (21) or the downstream protein SMADs, and then promotes the proliferation, apoptosis, angiogenesis, and invasion of tumor cells through TGF-β signal transduction pathway (22)(23)(24), which might explain its wide involvement in tumorigenesis, including that of cervical cancer. In the present study, the recombination plasmid of PCDNA3.1-RUNX3 was constructed and successfully transfected into Hce1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which RUNX3 acts in cervical cancer have not been reported. Transcription factor of RUNX3, which is a downstream effector of TGF-β, acts on the TGF-β receptor type II (21) or the downstream protein SMADs, and then promotes the proliferation, apoptosis, angiogenesis, and invasion of tumor cells through TGF-β signal transduction pathway (22)(23)(24), which might explain its wide involvement in tumorigenesis, including that of cervical cancer. In the present study, the recombination plasmid of PCDNA3.1-RUNX3 was constructed and successfully transfected into Hce1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that RUNX3 is a downstream effector of TGF-β and Notch signaling pathways, and plays critical roles in regulating cell functions, such as angiogenesis, cell migration and apoptosis (14,15,17,25). Our results showed that TGF-β and Notch signaling were activated during the hypoxia-induced EndMT of HCMECs.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately a decade ago RUNX3 was claimed to be a tumor suppressor that inhibited the expression of vascular endothelial growth factor (VEGF) and reduced the angiogenesis, growth, and metastasis of human gastric cancer (13). RUNX3 is a direct target gene of Notch in human endothelial cells and a downstream effector of the TGF-β signaling pathway, and plays a critical role in angiogenesis, cell migration and invasion (14,15). Recent studies suggest that RUNX3 knockdown enhances endothelial progenitor cell (EPC) function and that miR-130a regulates EPC autophagy through RUNX3 (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Three members of the runt‐related transcription factor (RUNX) family genes, RUNX1 , RUNX2 , and RUNX3 transcription factors, are known as important developmental regulators in the inception and progression of a variety of human cancers . RUNX3 is a tumor suppressor gene that participates in the regulation of cell proliferation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Three members of the runt-related transcription factor (RUNX) family genes, RUNX1, RUNX2, and RUNX3 transcription factors, are known as important developmental regulators in the inception and progression of a variety of human cancers. 4 RUNX3 is a tumor suppressor gene that participates in the regulation of cell proliferation and apoptosis. It has been reported that the changes in RUNX3 protein levels or functions are associated with various epithelial cancers, Abbreviations: LSCC, Laryngeal squamous cell carcinoma; RUNX3, Runt-related transcription factor 3; DNMTs, DNA (cytosine-5-)-methyltransferases; miRNA, microRNA; 3′-UTR, 3′ untranslated region; FBS, fetal bovine serum including LSCC.…”
Section: Introductionmentioning
confidence: 99%